2021
DOI: 10.1109/access.2021.3114713
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Communications for Improving the Performance of Bidirectional Full-Duplex System With Multiple Reconfigurable Intelligent Surfaces

Abstract: In this paper, we exploit the benefits of full-duplex (FD) transmission and reconfigurable intelligent surfaces (RISs) by considering a bidirectional full-duplex wireless communication system with the support of RISs. Specifically, cooperative communications are applied at two FD terminals in a RISsassisted bidirectional full-duplex (RIS-FD) system. In this context, we successfully derive the mathematical expressions of the outage probability (OP) and the ergodic capacity (EC) of the RIS-FD system with a direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Recently, traditional reflecting-only RIS aided FD systems have attracted considerable interest. In [35], the authors derived outage probability and ergodic capacity of a bidirectional FD system with multiple RISs. In [36], the authors studied the sum rate maximisation (SRM) for an RIS aided FD MIMO system.…”
Section: Literature Review and Background Workmentioning
confidence: 99%
“…Recently, traditional reflecting-only RIS aided FD systems have attracted considerable interest. In [35], the authors derived outage probability and ergodic capacity of a bidirectional FD system with multiple RISs. In [36], the authors studied the sum rate maximisation (SRM) for an RIS aided FD MIMO system.…”
Section: Literature Review and Background Workmentioning
confidence: 99%
“…In this research, the proposed system model with the energy harvesting (EH) and information processing (IT) is illustrated as shown in [19]- [25]. The proposed system model is drawn in Figure 1 and the time switching protocol is presented in Figure 2.…”
Section: System Modelmentioning
confidence: 99%
“…Simulation results showed that RIS joined with the FD relay was superior to other cases. Based on the previous inferences, the authors of [ 21 , 22 , 23 , 24 , 25 , 26 ] considered the union of RIS and FD technology and demonstrated the performance gains. To name a few, the authors of [ 21 ] proposed an SI mitigation method in RIS-assisted FD system, thus mitigating the strong SI to feed in the analog-to-digital converters of finite bit resolutions.…”
Section: Introductionmentioning
confidence: 99%
“…To name a few, the authors of [ 21 ] proposed an SI mitigation method in RIS-assisted FD system, thus mitigating the strong SI to feed in the analog-to-digital converters of finite bit resolutions. The authors of [ 22 ] formulated the mathematical expressions of outage probability and ergodic capacity. They concluded that RIS could indirectly diminish the adverse consequence of the residual SI and ameliorate the performance in the FD system.…”
Section: Introductionmentioning
confidence: 99%